Prevalence of Metabolic Syndrome in Patients present with Unstable Angina (Medical Forum Monthly, 2024)
Objective: The main objective of this study was to determine the frequencyof metabolic syndrome in patients presesnting with unstable angina at DUHS. Study Design: Cross-sectional observational study. Place and Duration of Study: This study was carried out at all medical wards of a DUHS from January 2012 to July 2012. Materials and Methods: 81 patients with Unstable Angina (UA) presented in medical ward that fulfilled the inclusion and exclusion criteria and gave informed consent were enrolled for the study. Metabolic syndrome was defined according to ATPIII criteria. Patients were evaluated for obesity, diabetes, hypertension, hypertriglyceridemia and low HDL. Results: Total 81 patients with unstable angina were included in this study Out of them 43 (53.1%) were male and 38 (46.9%) were female. Mean age was 60.23 ± 8.7. Majority of patients (49.4%) were lying in 51 to 60 years age group. The frequency of metabolic syndrome was thirty nine (48.1%). Among them twenty three (53.5%) were male and sixteen (42.1%) were females, hence it shows insignificant p value of 0.018. Conclusion: Metabolic syndrome is common with high frequency in our population. This study provides a quantitative estimate of the frequency of metabolic syndrome and suggests Diabetes, low HDL, hypertension, hypertriglyceridaemia and obesity strongly correlates with unstable angina.